Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board. Part XV Chemical Pulps and Writing and Printing Papers from Albi la stipulata, Boivin - Bhat, R. V.; Guha, S. R. D. (Indian Forester, 1953)
Laboratory experiments on the production of chemical pulps by the sulphate process from the wood of Albi ia stipulata are described. The wood was obtained from forests of Bihar. Results of four pilot plant experiments on the preparation of writing and printing papers from this wood are also included. This investigation has shown that chemical pulps in satisfactory yields can be prepared from this wood. The whiteness of the bleached pulps was good. Although the average fibre length of the pulps was only 1.02 mm., writing and printing papers made on the pilot plant from the furnish containing entirely the pulp from this wood were characterized by good strength properties. The formation of the papers was satisfactory. Two samples of papers - one writing and the other printing - are appended in this bulletin.